Reprogrammable meta-hologram for optical encryption - Qu, Geyang; Yang, Wenhong; Song, Qinghai; Liu, Yilin; Qiu, Cheng-Wei; Han, Jiecai; Tsai, Din-Ping; Xiao, Shumin (Nature communications, 2020)
Meta-holographic encryption is a potentially important technique for information security. Despite rapid progresses in multi-tasked meta-holograms, the number of information channels available in metasurfaces is limited, making meta-holographic encryption vulnerable to some attacking algorithms. Herein, we demonstrate a re-programmable metasurface that can produce arbitrary holographic images for optical encryption. The encrypted information is divided into two matrices. These two matrices are imposed to the incident light and the metasurface, respectively. While the all-dielectric metasurface is static, the phase matrix of incident light provides additional degrees of freedom to precisely control the eventual functions at will. With a single Si metasurface, arbitrary holographic images and videos have been transported and decrypted. We hope that this work paves a more promising way to optical information encryption and authentication. Here, the authors demonstrate a re-programmable metasurface that can produce arbitrary holographic images for optical encryption. The encrypted information is divided into two matrices and defined to the incident laser to produce arbitrary holographic images.